Power system safety management and audit protocols - Arshad, M.; Islam, Syed; Khaliq, A. (Curtin University of Technology, 2007)
The major objective of a safety audit is to determine the effectiveness of the company's safety and loss prevention measures. Identifying potential electrical hazards to prevent or minimize loss of life and property is perceived seriously by the utilities world wide. Safety audit is a methodical approach to evaluate potential hazards enabling suggestions for improvement. It is an important tool for identifying deterioration of standards, areas of risks or vulnerability, hazards and potential incidents in plants for determining necessary action to minimize hazards ensuring effective and meaningful safety efforts. A comprehensive electrical safety audit provides a thorough review of the utility installations, identifies potential electrical hazards, flaws in design system, maintenance system, etc. This paper presents a safety management system and audit protocols to design, plan and execute the electrical safety audit program.